Depletion of Rad54, DNA PKcs and tankyrase 1 by small interfering RNA and the effects of radiation-induced mutagenesis, toxicity and telomere function in human cells - Zhou, Junqing, author; Liber, Howard L., advisor; Bailey, Susan M., committee member; Roess, Deborah A., committee member; Fox, Michael H., committee member (Colorado State University. Libraries, 2007)
The double-strand break (DSB) is one of the most severe types of DNA damage. Incorrect repair of such lesions results in chromosomal rearrangements and mutations that can lead to cancer and heritable defects in the progeny. There also is evidence that DNA DSBs are induced in bystander cells, which have not been directly irradiated but nevertheless respond to their exposed neighbors. Studies have suggested that the bystander response is potentially tumorigenic. Small interfering RNA (siRNA) was used to silence expression of two genes, Rad54 and DNA-PKcs, that are known to be involved in DSB repair pathways and then the phenotypic consequences were examined in cells with different p53 status and also in directly irradiated and bystander cells. In directly irradiated cells, knockdown of Rad54 resulted in increased radiosensitivity in WTK1 (mutant p53), but this did not occur in TK6 (wild type p53) or NH32 (null p53) cells. Importantly, the radiosensitivity of Rad54-deficiency in WTK1 cells was evident in the S/G2 phases of the cell cycle but not in G1 phase. The immunoprecipitation studies showed that mutant p53, as well as wild type p53, associates with Rad54. Mutagenesis caused by deficiency of Rad54 and DNA-PKcs in directly irradiated and bystander cells was studied. For directly irradiated mutagenesis, knockdown of Rad54 led to increased ionizing radiation (IR)-induced mutation at the autosomal heterozygous thymidine kinase (tk) locus in WTK1 and NH32 cells, but the knockdown did not affect mutagenesis in p53 wild-type TK6; knockdown of DNA-PKcs led to increased IR-induced mutation in WTK1 cells but mutagenesis was decreased in TK6 and NH32 cells. For bystander mutagenesis, the incubation of WTK1 bystander cells with unirradiated WTK1, TK6 or NH32 donor cells did not alter the background mutation fraction in bystander cells. The same was true for TK6 and NH32 bystander cells cultured with unirradiated WTK1, TK6 and NH32 donor cells. Co-culture with directly irradiated donor cells led to increases in mutation fraction in all three bystander cell lines regardless of p53 status. Knockdown of DNA-PKcs and Rad54 in the three irradiated donor cell lines resulted in no effect on bystander mutagenesis, suggesting that DNA repair status in donor cells is not important. However, the DNA DSB repair status in bystander cells did turn out to be important. Knockdown of DNA-PKcs resulted in increased bystander mutagenesis in all three cell lines, but knockdown of Rad54 did not result in increased bystander mutagenesis. Increasing evidence has accumulated to show that some DSB repair proteins are required for normal function of mammalian telomeres and that some telomere maintenance proteins also serve as modulators of the cellular responses to DSB damage. siRNA was used to knock down tankyrase 1, a protein known to be involved in telomere elongation and maintenance, and phenotypic consequences on the processes of DNA damage response/repair were examined. Knockdown of tankyrase 1 resulted in an increased frequency of telomere sister-chromatid exchanges. Knockdown of tankyrase 1 also resulted in an increase in radiosensitivity and IR-induced mutagenesis. Surprisingly, knockdown of tankyrase 1 decreased levels of DNA-PKcs, and this may account for the observed phenotypic changes.
Keywords: molecular biology; cellular biology